ORGANIC AGRICULTURE AS AN INDICATOR OF SUSTAINABLE AGRICULTURAL DEVELOPMENT: SERBIA IN FOCUS - Tomaš Simin, Mirela; Rodić, Vesna; Glavaš-Trbić, Danica (Economics of Agriculture, 2019)
Sustainable development is a concept which has not yet been uniquely defined at the international level. As a result, it is difficult to define the indicators which could "measure" the achievement of sustainability. The paper deals with organic agriculture as a commonly used indicator of sustainable agricultural development. The organic farming in Serbia is legally a well-regulated area, but still not developed to the necessary and possible extent. Following the practice of the most developed countries, the area under organic production is distinguished as one of the indicators in the National List of Indicators for Sustainable Development of the Republic of Serbia. Nowadays, organic farming occupies only about 0.45% of total UAA in Serbia (approx 15,000 ha), which is relatively low in comparison with the EU countries. Therefore, the development of Serbian agriculture cannot be assessed as sustainable. Although the authors of this paper support the use of organic agriculture as an indicator of agricultural sustainability, they endorse it in conjunction with other indicators in the matter, whenever possible